OPERATIONALISING MEDIEVAL LEXICOGRAPHY AND FOLK LINGUISTICS: A PROVENANCE-BASED FRAMEWORK FOR THE ANALYSIS OF SEMANTIC OPPOSITION IN ARABIC - Sirojiddin Sotvoldiev (International Journal of Literature and Language Studies, 2026)
Abstract. The study investigates semantic opposition in Arabic through an integrated framework that combines medieval lexicographical traditions with contemporary folk-linguistic approaches. Classical Arabic scholarship, particularly the lexicographical methodology of Ibn Duraid in Jamharat al-Lugha, provides a rich account of semantic contradiction and oppositional relations among lexical items. At the same time, modern folk-linguistic research demonstrates that speakers’ beliefs, cultural practices, and evaluative judgments significantly influence semantic interpretation. Despite the importance of both traditions, little attention has been paid to developing a unified methodological framework capable of integrating historical lexicographical procedures with contemporary corpus evidence and ethnographic data. This study proposes a provenance-based annotation model that operationalises Ibn Duraid’s analytical procedures and incorporates folk-linguistic metadata to distinguish lexical antonymy, pragmatic exclusion, and culturally mediated opposition. The proposed framework demonstrates how historical linguistic knowledge can be transformed into a reproducible analytical tool suitable for corpus-based semantic research and language documentation.